THE INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON PURCHASING DECISIONS WITH CONSUMER TRUST AS AN INTERVENING VARIABLE ON XIAOMI SMARTPHONES (Case Study at Mi Shop Tebing Tinggi City) - Benhart Nainggolan; Suwadi (RADJA PUBLIKA, 2024)
This study aims to analyze